2017
DOI: 10.1038/nature24470
|View full text |Cite
|
Sign up to set email alerts
|

Kctd13 deletion reduces synaptic transmission via increased RhoA

Abstract: Copy-number variants of chromosome 16 region 16p11.2 are linked to neuropsychiatric disorders1–6 and are among the most prevalent in autism spectrum disorders1,2,7. Of many 16p11.2 genes, Kctd13 has been implicated as a major driver of neurodevelopmental phenotypes8,9. The function of KCTD13 in the mammalian brain, however, remains unknown. Here we delete the Kctd13 gene in mice and demonstrate reduced synaptic transmission. Reduced synaptic transmission correlates with increased levels of Ras homolog gene fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
174
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(180 citation statements)
references
References 66 publications
5
174
1
Order By: Relevance
“…These results suggest that KCTD13 may recruit RhoA for modulating its turnover via the cullin‐3 ubiquitin ligase, thereby regulating synaptic function, consistent with spatiotemporal network analysis of brain subregions . This Kctd13 ‐knockout mouse (entire Kctd13 gene deleted) lacked detectable memory deficits . However, an independently constructed Kctd13 ‐deficient mouse with an out‐of‐frame exon 2 deletion (expected to fully ablate Kctd13 ) exhibited deficits in short‐term recognition memory, but lacked detectable changes in expression levels of RhoA, the candidate KCTD13‐cullin target substrate .…”
Section: Kctd Genes Associated With Neurodevelopmental and Neuropsychsupporting
confidence: 66%
See 2 more Smart Citations
“…These results suggest that KCTD13 may recruit RhoA for modulating its turnover via the cullin‐3 ubiquitin ligase, thereby regulating synaptic function, consistent with spatiotemporal network analysis of brain subregions . This Kctd13 ‐knockout mouse (entire Kctd13 gene deleted) lacked detectable memory deficits . However, an independently constructed Kctd13 ‐deficient mouse with an out‐of‐frame exon 2 deletion (expected to fully ablate Kctd13 ) exhibited deficits in short‐term recognition memory, but lacked detectable changes in expression levels of RhoA, the candidate KCTD13‐cullin target substrate .…”
Section: Kctd Genes Associated With Neurodevelopmental and Neuropsychsupporting
confidence: 66%
“…However, an independently constructed Kctd13 ‐deficient mouse with an out‐of‐frame exon 2 deletion (expected to fully ablate Kctd13 ) exhibited deficits in short‐term recognition memory, but lacked detectable changes in expression levels of RhoA, the candidate KCTD13‐cullin target substrate . However, RNA‐seq analyses of gene expression profiles from the cortex and hippocampus of Kctd13 ‐deficient (exon 2‐deleted) mice revealed altered signaling pathways critical for neurodevelopment, including synaptic formation, and both knockout mouse lines exhibited reduced spine density in the hippocampus . Thus, further studies are required to understand the mechanistic complexities by which Kctd13 copy number modulates brain development beyond RhoA signaling.…”
Section: Kctd Genes Associated With Neurodevelopmental and Neuropsychmentioning
confidence: 99%
See 1 more Smart Citation
“…The KCTD7 -related KCTD13 gene at 16p11.2 is thought to have a role in a small subset of autism cases. 1 Any manifestations of heterozygous KCTD7 mutations in late onset disorders analogous to heterozygous loss of progranulin in older adults with frontotemporal dementia/FTD versus bi-allelic mutations that cause lipofuscinosis CLN11 44 are unexplored. Based on yeast studies that first identified the KCTD-like yeast Whi2, 5 KCTD7 variants could potentially compensate for more deleterious mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Several KCTD family proteins including KCTD7 have been reported to bind CUL3, 13, 16 consistent with structure modeling for other KCTDs. 15 In this capacity as potential cargo adaptors, several other KCTD family proteins have been suggested to target specific cargo proteins for degradation, 1 although most await confirmation. A similar role for KCTD7 is consistent with lysosome pathway defects in several other EPM and CLN disorders, 17, 18 and other neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 99%